(3GdYbO GdEdcJQhfj (B/s - (3eUWai CMeO EHQGgjes; (3eMeO GdSYjO QTOjs; (3LGeYI GdefjGs (3cdjI GdMbhbs ((3GdefjG (B:s (3cdjI GdMbhb (B- (3LGeYI GdefjG,s, 2009)
(3jYO GdYbO Chd eUGOQ GdGdJRGe hCgegG; MjK jMXi HJfXje JTQjYj aj eNJda HdOGf GdYGde, aGdYbO ef CcKQ GdCfXeI TjhkYG ai GdMjGI GdjhejI, hGdeUOQ GdCSGSj dfTCI GdMbhb hGdEdJRGeGJ, hJXgQ CjkVG gPg GdCgejI aj GYJHGQg ef GdCSS GdJj jbhe YdjgG GdfTGW GdGbJUGOj aj GdeLJeY, agh COGI ddeHGOdI hGdJYGhf Hjf CaQGO GdeLJeY hWhGFaI(B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdefjG (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfj (B2009.s
(3HHdjhLQGajG(B: (3UaMGJ (B478 -495.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdYbO GdEdcJQhfjs; (3GdYbO GdNWjs; (3GdEjLGH GdEdcJQhfjs; (3GdbHhd GdEdcJQhfjs; (3GdeMd GdEdcJQhfjs; (3EKHGJ GdYbO GdEdcJQhfjs; (3GdJhbjY GdEdcJQhfjs; (3JhKjb GdYbO GdEdcJQhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdefjGs -- (3GdbGfhf GdeOfjs